(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This is a case study of the current living conditions of nine rural families displaced from the “Garrapatal” village, in the municipality of La Palma Cundinamarca, returned through the land restitution policy. Methods of collecting information from primary sources such as the focus group and closed surveys were used, which were transcribed for their categorical analysis and generated results related to the ages of the returned population, factors that motivated the return, the current conditions of these families in housing, security, economic sustainability, health, education, among others; as wellas the reasons that generated that a segment formed by the youngest members of these families did not return, reaching conclusions about the progress and difficulties presented in the restoration of their rights, uprooting, the transformation of peasant identities.